Respuesta :
Step-by-step explanation:
First, subtract
7
from each side of the equation to put the equation in standard form:
x
2
+
4
x
+
4
−
7
=
7
−
7
x
2
+
4
x
−
3
=
0
We can now use the quadratic formula to find the solutions for
x
. The quadratic formula states:
For
a
x
2
+
b
x
+
c
=
0
, the values of
x
which are the solutions to the equation are given by:
x
=
−
b
±
√
b
2
−
(
4
a
c
)
2
⋅
a
Substituting:
1
for
a
4
for
b
−
3
for
c
gives:
x
=
−
4
±
√
4
2
−
(
4
⋅
1
⋅
−
3
)
2
⋅
1
x
=
−
4
±
√
16
−
(
−
12
)
2
x
=
−
4
±
√
16
+
12
2
x
=
−
4
±
√
28
2
x
=
−
4
±
√
4
⋅
7
2
x
=
−
4
±
√
4
√
7
2
x
=
−
4
±
2
√
7
2
x
=
−
4
2
±
2
√
7
2
x
=
−
2
±
√
7
Or
x
=
−
2
+
√
7
and
x
=
−
2
−
√
7